Reduced inhibitory gate in the barrel cortex of Neuroligin3R451C knock‐in mice, an animal model of autism spectrum disorders. Issue 7 (17th July 2014) - Cellot, Giada; Cherubini, Enrico
Abstract Neuroligins are postsynaptic adhesion molecules that interacting with presynaptic neurexins ensure the cross‐talk between pre‐ and postsynaptic specializations. Rare mutations in neurexin–neuroligin genes have been linked to autism spectrum disorders (ASDs). One of these, the R451C mutation of the gene encoding for Neuroligin3 (Nlgn3), has been found in patients with familial forms of ASDs. Animals carrying this mutation (NL3R451C knock‐in mice) exhibit impaired social behaviors, reminiscent of those observed in ASD patients, associated with major alterations in both GABAergic and glutamatergic transmission, which vary among different brain regions and at different developmental stages. Here, pair recordings from parvalbumin‐ (PV) expressing basket cells and spiny neurons were used to study GABAergic synaptic signaling in layer IV barrel cortex of NL3R451C mutant mice. We found that the R451C mutation severely affects the probability of GABA release from PV‐expressing basket cells, responsible for controlling via thalamo‐cortical inputs the feed‐forward inhibition. No changes in excitatory inputs to parvalbumin‐positive basket cells or spiny neurons were detected. These data clearly show that primary targets of the NL3 mutation are PV‐expressing basket cells, independently of the brain region where they are localized. Changes in the inhibitory gate of layer IV somatosensory cortex may alter sensory processing in ASD patients leading to misleading sensory representations with difficulties to combine pieces of information into a unified perceptual whole.